Effects of Different Selenium Sources on Laying Performance, Egg Selenium Concentration, and Antioxidant Capacity in Laying Hens - Meng, Tiantian; Liu, Yi-lin; Xie, Chun-yan; Zhang, Bin; Huang, Yi-qiang; Zhang, Ya-wei; Yao, Yajun; Huang, Ruilin; Wu, Xin (Biological trace element research, 2019)
Supplementation of selenium (Se) is a common practice in the poultry industry via sodium selenite (SS) and selenium yeast (SY), while the effects of nano-selenium (NS) on laying hens are poorly known. This study aimed to compare the effects of NS, SS, and SY on productivity; selenium (Se) deposition in eggs; and antioxidant capacity in laying hens. A total of 288 30-week-old Brown Hy-line laying hens were randomly assigned into four dietary treatments, which included corn-soybean meal basal diet (Con) without Se sources and basal diets supplemented with 0.3 mg Se/kg as SS, SY, or NS, respectively. The results exhibited that Se-supplemented treatments achieved greater egg production, egg weight, and daily egg mass, also better feed conversion ratio than Con group ( p < 0.05). Se supplementation significant increased egg Se concentration and decreased the egg Se deposition efficiency ( p < 0.05), while SY or NS supplementation had higher Se deposition efficiency than SS group at 35 days ( p < 0.05). Moreover, serum glutathione peroxidase (GSH-Px) activity increased in SS or NS group compared to Con group ( p < 0.05). The glutathione peroxidase 4 (GPX-4) mRNA levels in liver were significantly higher ( p < 0.05) in SS or SY group than in NS group, and mRNA levels of the methionine (Met) metabolism gene glycine N-methyltranserfase (GNMT) were markedly upregulated ( p < 0.05) in SY group compared to SS or NS group. Taken together, the results revealed Se from SY is deposited into eggs more efficiently than Se from NS or SS, probably via enhancing the route of Met metabolism. Meanwhile, it might be concluded that SS or SY supplementation directly regulated GSH-Px activity via enhancing GPx4 level, whereas NS via GPx1, thus affecting body oxidation and development.